Mechanisms of Peripheral and Central Pain Sensitization: Focus on Ocular Pain - Puja, Giulia; Sonkodi, Balazs; Bardoni, Rita (Frontiers in Pharmacology, 2021)
Persistent ocular pain caused by corneal inflammation and/or nerve injury is accompanied by significant alterations along the pain axis. Both primary sensory neurons in the trigeminal nerves and secondary neurons in the spinal trigeminal nucleus are subjected to profound morphological and functional changes, leading to peripheral and central pain sensitization. Several studies using animal models of inflammatory and neuropathic ocular pain have provided insight about the mechanisms involved in these maladaptive changes. Recently, the advent of new techniques such as optogenetics or genetic neuronal labelling has allowed the investigation of identified circuits involved in nociception, both at the spinal and trigeminal level. In this review, we will describe some of the mechanisms that contribute to the perception of ocular pain at the periphery and at the spinal trigeminal nucleus. Recent advances in the discovery of molecular and cellular mechanisms contributing to peripheral and central pain sensitization of the trigeminal pathways will be also presented.